KASUS PEMBEGALAN TERHADAP MAHASISWA UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA MEDAN - Ferdinandus Bani; Theofilla Tasya Oeleu; Ignecya Thithania Katoda; Christian Umbu Limu; Benediktus Peter Lay (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
This research investigates incidents of attacks on students at the University of North Sumatra (UMSU) in Medan City; This is intended for analysis. Focus on factors, namely influencing factors and actionable improvement strategies. This investigation method involves sources who investigate robbery cases in Medan City. The research results show that there is a relationship between factors such as street lighting, traffic density, and personal safety behavior and the frequency of robberies. The implications of these findings can be used to develop more urban safety measures.